Case Report and Literature Review on Tongue Schwannoma - Michelangelo Pierri; Antonio Moffa; Lorenzo Sabatino; Francesco Iafrati; Simone Di Giovanni; Luigi De Benedetto; Manuele Casale (Journal of Otorhinolaryngology, Hearing and Balance Medicine)
Schwannoma is a neoplasm originating from cells surrounding and insulating axons in peripheral nerves. It usually presents benign behaviour with slow growth. A significant portion of cases occur in the head and neck region but rarely in the oral cavity, where the tongue is the most frequently affected organ. This article describes the case of a man presenting an asymptomatic mass on the dorsal aspect of the tongue that sought attention at the Integrated Therapies in Otorhinolaryngology Department of the Policlinico Campus Bio-Medico Foundation in Rome. After clinical and radiological examinations, the patient underwent surgical treatment under local anaesthesia. A literature search was conducted on PubMed and Google Scholar. Only complete case reports published in English from 1923 to 2023 were selected. A total of 183 cases were considered after the selection of relevant articles and the elimination of duplicates. The resulting data confirm that the most common presentation of this pathology consists of a painless mass in the oral tongue; usually, this lesion is removed surgically via a transoral approach, but different variations were described depending on the dimensions and position of the lesion.